Patronage by Augustus and the Heirs of the Princeps in the Hispanic Civic Communities - Enrique Melchor Gil (Gerión, 2017)
This is a study on the established relationship in civic patronage between the members of the imperial family and the different Hispanic towns. We question if some of such relations have their origins in the time of Cesar, just when Octavius was trying to attain the power or during the first years of his principate. Likewise we attempt to show how the relations of patronage were successively transmitted by the different heirs appointed by Augustus to succeed him: Agrippa, Caius and Lucius Caesar, or Tiberius. Finally we analyse the reasons why the imperial patronage came to disappear, being replaced by other new implements of power, like the worship to the Emperor or to Rome and Augustus, allowing the ruling dynasty to glorify extremely their power, and so, to guarantee its continuity.